2013
DOI: 10.1002/fsn3.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium benzoate on storage stability of previously improved beverage from tamarind (Tamarindus indica L.)

Abstract: The effect of sodium benzoate on the quality attributes of improved tamarind beverage during storage was investigated. Tamarind beverages were produced according to a previously reported improved method, with or without chemical preservatives (100 mg/100 mL sodium benzoate). Tamarind beverage produced according to traditional processing method served as the control. The tamarind beverages were stored for 4 months at room (29 ± 2°C) and refrigerated (4–10°C) temperatures. Samples were analyzed, at regular inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Thus, use of herbicide and food additives in diet can contribute to reproduction of pathogenic and conditionally pathogenic microorganisms (staphylococcus, streptococcus, yeast-like fungi, enterobacteria and others) which are present in the macroorganism as facultative and transitional microflora. This can lead (Sekirov et al, 2010;Adeola & Aworh, 2013;Suez et al, 2014;Nettleton et al, 2016) to possible pathologies in the gastrointestinal tract, diseases of cardio-vascular system, disorder in metabolism, allergies and autoimmune diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, use of herbicide and food additives in diet can contribute to reproduction of pathogenic and conditionally pathogenic microorganisms (staphylococcus, streptococcus, yeast-like fungi, enterobacteria and others) which are present in the macroorganism as facultative and transitional microflora. This can lead (Sekirov et al, 2010;Adeola & Aworh, 2013;Suez et al, 2014;Nettleton et al, 2016) to possible pathologies in the gastrointestinal tract, diseases of cardio-vascular system, disorder in metabolism, allergies and autoimmune diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of these substances on the organisms of humans and animals is described in a number of studies. The most broadly used preservative is sodium benzoate (Е 211 ) which has antimicrobial and fungicidal effects, significantly inhibiting yeasts and yeast fungi (Adeola & Aworh, 2013). Non-caloric artificial sweeteners (NAS), particularly saccharin (Е 954 ), are some of the most broadly used food additives in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Color changes during storage also occured in functional drinks from a mixture of cucumber and melon (Kausar et al, 2012). Research conducted by Adeola & Aworh (2014) showed that consumer acceptance of the color aspect of the tamarind drink added with benzoate decreased with the longer storage time. The darker color change is strongly suspected because of enzymatic browning, strongly correlated with the total phenolics content (Persic et al, 2017).…”
Section: Colormentioning
confidence: 99%
“…The beverage was packaged in sterilized glass bottles, corked, and pasteurized at 95°C for 8 min, cooled and stored to serve. This method was improved with greater storability up to 14 weeks without hampering nutritional quality (carotenoids, beta carotene, lycopene) with good color, ascorbic acid content (less sour) and sweetness over the traditionally used method of preparation where concentrated pulp was extracted, sieved, filtered, diluted(1:100) and heated in open pot at 40oC with high sugar content (275g), cooled and packed [16].…”
Section: Tamarind Drinksmentioning
confidence: 99%